2006
DOI: 10.1182/blood-2006-07-034405
|View full text |Cite
|
Sign up to set email alerts
|

Late cardiotoxicity after treatment for Hodgkin lymphoma

Abstract: We assessed cardiovascular disease (CVD) incidence in 1474 survivors of Hodgkin lymphoma (HL) younger than 41 years at treatment . Multivariable Cox regression and competing risk analyses were used to quantify treatment effects on CVD risk. After a median follow-up of 18.7 years, risks of myocardial infarction (MI) and congestive heart failure (CHF) were strongly increased compared with the general population (standardized incidence ratios [SIRs] ‫؍‬ 3.6 and 4.9, respectively), resulting in 35.7 excess cases o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
456
5
20

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 654 publications
(494 citation statements)
references
References 53 publications
13
456
5
20
Order By: Relevance
“…7,22,23 Two recent large cohort studies from the Netherlands and UK show an increased standardized mortality rate in CVD that is probably attributed to radiotherapy and adriamycin. 5,4 The UK study also found a significant relation to vincristin. 4 The Dutch study, which was a matched control study, found that there was a general increase in the risk for in patient care for CVD in patients treated for HL.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…7,22,23 Two recent large cohort studies from the Netherlands and UK show an increased standardized mortality rate in CVD that is probably attributed to radiotherapy and adriamycin. 5,4 The UK study also found a significant relation to vincristin. 4 The Dutch study, which was a matched control study, found that there was a general increase in the risk for in patient care for CVD in patients treated for HL.…”
Section: Discussionmentioning
confidence: 59%
“…The risk is particularly high in patients treated before the age of 40 years. [4][5][6][7][8] If given high doses, radiotherapy (RT) damages the endothelial cells, causes fibrosis of the valves, and induces myocardial injury and cardiomyopathy. 9 Therapy with adriamycin is a known risk factors for the development of cardiomyopathy.…”
mentioning
confidence: 99%
“…16,21,23 CAD risk begins to increase during the first five years after irradiation and continues for at least 20 years. 21,22 There is no statistically significant difference between patients with or without risk factors for CAD at the time of radiotherapy. 22 The increase in CAD is directly proportional to the average dose of radiation and heart volume included in the RT field.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Incidental exposure of the heart to RT increases the incidence of accelerated or premature coronary artery disease (CAD), [20][21][22] commonly identified in young or relatively young patients with none of the major risk factors for atherogenesis, such as smoking, diabetes mellitus, dyslipidemia, hypertension and a family history of early atherosclerosis. 16,21,23 CAD risk begins to increase during the first five years after irradiation and continues for at least 20 years.…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…In a study of Hodgkin's lymphoma survivors, the actuarial risk of congestive heart failure 25 years after diagnosis was 0.4% with non-anthracycline chemotherapy without mediastinal radiotherapy, 7.5% with non-anthracycline chemotherapy and concurrent mediastinal radiotherapy, and 10.7% with anthracyclines and mediastinal radiotherapy. 11 …”
Section: Box 1: Unanswered Questions About Cancer Treatment In Teenagmentioning
confidence: 99%